PENGARUH VARIABILITAS HARGA POKOK PENJUALAN, RASIO LANCAR, VARIABILITAS PERSEDIAAN, PERPUTARAN PERSEDIAAN TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN - Shofyah Shofyah; Nur Hidayati; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTIONIn Financial Accounting Standards, inventory is one asset that has a fairly large value and is an important asset both in number and role in company activities. Inventory is also an important part of the company's activities, both trading companies and manufacturing companies, because inventory of one asset is very important as a source of corporate income. The purpose of this study is to determine the effect of cost of goods sold, current ratio, inventory variability, inventory turnover to the selection of inventory accounting methods. The object of this study consists of manufacturing companies listed on the Indonesian stock exchange from 2015-2017. The method used is statistics that aim to test hypotheses using the logistic regression method. According to the Statement of Financial Accounting Standards (PSAK) No. 14 (revised 2015), inventories are assets available for sale in terms of raw materials or equipment for use in the process or provision of services. The AVERAGE accounting method is used by most manufacturing companies. The AVERAGE method is used by 13 sample companies, while the FIFO method is used by 5 sample companies. Keywords: Cost of goods sold, current ratio, inventory variability, inventory turnover.